Qingre Huoxue decoction attenuates myocardial ischemia‒reperfusion injury by regulating the autophagy‒endoplasmic reticulum stress axis via FAM134B-mediated ER-phagy - Li, Rui; Zhang, Jiechun; Ji, Shuliang; Fang, Junfeng; Ji, Xiaodong; Zeng, Yanping; Liu, Nan; Wu, Wei; Liu, Shiyi (Frontiers in Pharmacology, 2024)
Background Autophagy‒endoplasmic reticulum (ER) stress axis dysregulation is linked to myocardial ischemia‒reperfusion injury (MIRI), which counteracts the benefits of acute myocardial infarction (AMI) reperfusion therapy. Qingre Huoxue decoction (QRHX) improves the short- and long-term prognosis of AMI after percutaneous coronary intervention and alleviates myocardial injury in AMI rats by stimulating autophagy via the PI3K/Akt pathway. We aimed to further explore the efficacy of QRHX in treating MIRI and its regulatory relationship with FAM134B-mediated ER-phagy. Materials and methods Rats were administered different concentrations of QRHX for 2 weeks, and then MIRI was induced. Ultra-performance liquid chromatography‒tandem mass spectrometry (UPLC‒MS) was used to examine the levels of the main pharmacological metabolites of the serum of rats treated with QRHX. H9c2 cells were pretreated with QRHX-mediating serum (QRHX-MS) for 24 h before being exposed to hypoxia/reoxygenation (H/R). The mechanisms underlying the effects of QRHX-MS were further studied via rescue experiments involving FAM134B knockdown. The myocardial infarct size, cardiac function, morphology and the expression of apoptosis-, autophagy-, and ER stress-related proteins and genes were assessed. The colocalization of autophagosomes with lysosomes and the localization of proteins involved in ER-phagy or autophagic flux was examined. Results QRHX decreased the myocardial infarct size and oxidative stress, improved cardiac function and alleviated morphological changes in a dose-dependent manner in MIRI rats by promoting autophagic flux to inhibit ER stress and ER stress-related apoptosis, which was related to FAM134B-mediated ER-phagy, as revealed by autophagy analysis. UPLC‒MS analysis of QRHX-MS revealed 20 major active metabolites of QRHX-MS, including baicalin, cryptotanshinone, 3,4-dihydroxybenzaldehyde and caffeic acid. QRHX-MS attenuated H/R-induced cardiomyocyte injury and apoptosis by increasing autophagic flux to suppress ER stress and ER stress-related apoptotic protein and gene expression. When autophagic flux was inhibited or FAM134B was knocked down in H9c2 cells followed by QRHX-MS pretreatment, the protective effect of QRHX was partially reversed. Conclusion QRHX alleviates myocardial injury, apoptosis and infarct size expansion in MIRI by regulating the autophagy‒ER stress axis via FAM134B-mediated ER-phagy.